2019
DOI: 10.1111/ecc.13037
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and survival following breast cancer

Abstract: Introduction Physical activity (PA) leads to improved survival in women following the diagnosis of breast cancer, but it is less clear whether PA has equally positive effects regardless of age at diagnosis. The purpose of our study was to evaluate the association between post‐diagnosis PA and survival in women aged below or over 55 years at diagnosis. Methods From a prospective population‐based cohort of Swedish women, we included 847 women, aged 34–84 years, who were diagnosed with breast cancer from 1992 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 20 publications
1
18
0
2
Order By: Relevance
“…We did find that being more physically active did reduce symptoms and improve well‐being. Lifestyle interventions, including exercise, reductions in sedentary time, yoga, cognitive retraining, and weight loss, have been shown to increase well‐being in other studies, so this remains an important topic for survivorship care visits …”
Section: Discussionmentioning
confidence: 99%
“…We did find that being more physically active did reduce symptoms and improve well‐being. Lifestyle interventions, including exercise, reductions in sedentary time, yoga, cognitive retraining, and weight loss, have been shown to increase well‐being in other studies, so this remains an important topic for survivorship care visits …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that physical activity has multiple benefits for breast cancer survivors, ranging from reducing fatigue [24,26,30] to increasing strength levels and improving quality of life [19,22,23]. [32].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been associated with a lower risk of developing breast cancer [9,[16][17][18][19], with a decrease in the probability of relapse and with a higher survival rate [16,[19][20][21]. In individuals with cancer, physical activity has benefits for their health: reduced fatigue, improved strength levels, and improved quality of life and physical function [17,19,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…PA has been related with better prognosis and survival in BC. Johnsson et al [ 139 ] studied 847 women aged 34 to 87 years old with BC, reporting a reduced all-cause mortality in the most active group. Importantly, their results showed that the improved survival of BC was only observed in women > 55 years, denoting the higher impact of PA in postmenopausal BC patients.…”
Section: The Association Of Pa With Bc Mortality and Survivalmentioning
confidence: 99%